Random keys Generating for Asymmetric Cryptography using Video Entropy: Random keys Generating for Asymmetric Cryptography using Video Entropy - Ismail Ahmed, Rasha; Mohammed, Rasha; Saba Fouad Hassan (Academic Science Journal, 2025)
Because of the widespread of the Internet usage and the emergence of multiple means of communication like Social media and email applications. also the rapid development in the field of communications lead to arising of difficulties, such as finding methods for protecting transmitted data and difficulty of controlling data penetration. Public key encryption methods are considered the most suitable techniques for correspondence over the Internet, but there is a major problem facing most of the methods of this system, which is the methods of exchanging keys between the sender and the recipient. In this paper, a new technique for generating keys proposed. by using some video properties to generate keys from data in the video randomly. The proposed method led to solve two problems at the same time. The first problem is the problem of exchanging keys, because sending the video via any means of communication does not raise the suspicion of the attacker, in addition to the difficulty of extracting the keys. The second problem is the methods of selecting the keys, because the proposed method generates many keys randomly.